PENINGKATAN KOMPETENSI LITERASI GURU SDS ISLAM TERPADU AZ-ZAHRA DEMAK - Kurniati, Lenny; Wahyuni, Arie; Hidayati, Destia Wahyu; Kusumawati, Ratih (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The competency improvement currently needed by teachers is literacy competency. Literacy competency in the world of education is very lacking and enthusiasm and motivation in the world of education is very minimal, so there is a need for training to increase literacy competency within teachers. This training to increase teacher competency was carried out at the Az-Zahra Integrated Islamic SDS Demak through direct provision of material and practice. All service teams provide knowledge and material related to literacy competencies needed by teachers. The result of this service is that teachers can develop literacy competencies in a comprehensive and detailed manner.